Perancangan Interface Sistem Absensi pada Chinchin Production menggunakan Extreme Programming (XP) - Rafael Ercole Hermanto; M. Zakki Abdillah (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Information system is an important component of any institution, a proper information system could bring a lot of benefits. An example of this is the attendance system. Chinchin Production faced a difficult challenge of managing human resources because previously employees had to sign their attendance manually, which is proven to be inefficient. The solution to this challenge is a proper attendance system to replace the old manual attendance system. The development methodology used is Extreme Programming (XP). Extreme Programming (XP) is an Agile project management methodology that aims for speed and simplicity. The prototype is designed using Unified Modeling Language (UML) as a modelling tool to visualize the structure of the system, as well as Figma to design the User Interface (UI) of the system. This attendance system helps Chinchin Production in managing human resources.